Biodiversity of Arunachal Pradesh and its Conservation - Koj Taro (Dera Natung Government College Research Journal)
he Northeast States of India and Arunachal Pradesh, in particular, are blessed with large numbers of rare and endemic species, for which region is recognized as a biodiversity hotspot. The region nurtures 5000 species of flowering plants, seven primates out of 16 found in the world, 770 species of birds etc. Due to various reasons, the species’ wide variety and variability and habitat are deteriorating with time: deforestation, encroachment, forest fire, illegal hunting and extraction, and rapid urbanization.